2014
DOI: 10.1002/jbmr.2359
|View full text |Cite
|
Sign up to set email alerts
|

Rates of and Risk Factors for Trabecular and Cortical BMD Loss in Middle-Aged and Elderly African-Ancestry Men

Abstract: Low trabecular (Tb) and cortical (Ct) volumetric BMD (vBMD) are related to increased fracture risk, but little is known about the patterns and correlates of Tb and Ct vBMD loss with aging. We examined the rates of change in total, Tb.vBMD and Ct.vBMD at the radius and tibia, and identified factors associated with vBMD loss among 1,569 men of African descent aged 40 years and older. Quantitative computed tomography was used to measure vBMD 6 years apart. The annualized rate of loss in Tb.vBMD was significant at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
5
1
Order By: Relevance
“…In contrast to our results, the Tobago Health Study of 1,569 men of African descent found weight gain was associated with greater loss of cortical vBMD at the radius and total vBMD at the tibia, assessed by pQCT (29) . The investigators hypothesized that weight gain related bone micro-damage, increased periosteal bone diameters, suppressed differentiation of mesenchymal stem cells into osteoblasts, decreased physical activity, and poor health status may account for the opposite association they observed between weight change and bone parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, the Tobago Health Study of 1,569 men of African descent found weight gain was associated with greater loss of cortical vBMD at the radius and total vBMD at the tibia, assessed by pQCT (29) . The investigators hypothesized that weight gain related bone micro-damage, increased periosteal bone diameters, suppressed differentiation of mesenchymal stem cells into osteoblasts, decreased physical activity, and poor health status may account for the opposite association they observed between weight change and bone parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…Bone loss trends were similar, although not always significant, for serum LDL-c concentrations. While the overall magnitude of effect was small for each association (1SD of cholesterol was associated with 0.1–0.5% difference in BMD measure), they are equivalent to the magnitude of effect of 10 years of increased age or a 1 SD greater body weight in the same population[27]. Therefore, we conclude that, in this population, serum lipid and lipoprotein cholesterols may have a potentially important association with BMD change.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, we excluded any man on lipid-lowering medication (N=52; 4%), androgen deprivation therapy (N=41; 3%), or both therapies (N=3) leaving 1289 men for the current analysis. Studies of the correlates of bone[24, 27] and cardiovascular health[28] in Tobago have been published previously. The Institutional Review Boards of the University of Pittsburgh and the Tobago Division of Health and Social Services approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…Cortical vBMD is a determinant of intrinsic stiffness of bone tissue. The rate of loss of cortical vBMD is steady or slower from 50 years till 75 years of age, compared to trabecular vBMD [ 30 , 31 ]. Though the US Caucasians were older, rural South Indian men had similar cortical vBMD and significantly lower trabecular vBMD.…”
Section: Discussionmentioning
confidence: 99%